Pseudo‐Waveform‐Selective Metasurfaces and their Limited Performance. Issue 1 (25th November 2020) - Nakasha, Tomoyuki; Phang, Sendy; Wakatsuchi, Hiroki
Abstract: In recent years, metasurfaces composed of lumped circuit components, including nonlinear Schottky diodes, have been reported to be capable of sensing particular electromagnetic waves even at the same frequency depending on their waveforms, or more specifically, their pulse widths. In this study, analogous waveform‐selective phenomena using only linear circuits and linear media are reported. Although such linear metasurfaces are analytically and numerically demonstrated to exhibit variable absorption performance, it cannot strictly be categorized as waveform‐selective absorption. It is due to the fact that the waveform‐selective responses in the linear metasurfaces originated from the dispersion behaviors of the structures rather than the frequency conversion seen in nonlinear waveform‐selective metasurfaces. These linear structures are thus referred to as pseudo‐waveform‐selective metasurfaces. Additionally, it is shown that the pseudo‐waveform‐selective metasurfaces have limited performance unless nonlinearity is introduced. These results and findings confirm the advantages of nonlinear waveform‐selective metasurfaces, which can be exploited to provide an additional degree of freedom to address existing electromagnetic problems/challenges involving even waves at the same frequency. Abstract : In this study, pseudo‐waveform‐selective phenomena using metasurfaces composed of only linear circuits and linear media are reported. Although such linear metasurfaces are analytically and numerically demonstrated to exhibit variable absorption performance, it cannot strictly be categorized as waveform‐selective absorption. Additionally, it is shown that the pseudo‐waveform‐selective metasurfaces have limited performance unless nonlinearity is introduced.